Adsorption of Ni2+ in aqueous solution by KMnO4 modified biomass: investigation on adsorption kinetics and modification mechanism. Issue 18 (11th August 2022) - Tong, Yuxing; Yan, Qunshan; Gao, Song; Xiong, Bin; Tang, Xiangbing; Liu, Zhichang; Li, Pengfei; Huang, Ming; Wang, Ziwei; Le, Xi; Pei, Wei; Dai, Zejun; et al.
ABSTRACT: In this study, KMnO4 modification was proved to effectively increase the Ni 2+ adsorption capacity of biomass. In order to clarify the KMnO4 modification mechanism, the Ni 2+ adsorption characteristics of KMnO4 modified corncob (PPCB) under adsorption time, pH and Ni 2+ concentration were studied. The results showed that the adsorption was the pseudo second-order kinetic process, indicating that chemisorption was the dominated process, which followed the Langmuir isotherm model and the highest Ni 2+ adsorption capacity of PPCB reached 35.6 mg/g. By KMnO4 modification, the corncob was oxidized to generate carboxylates, and the MnO2 (reduction product) was loaded on the modified corncob, both carboxylates and MnO2 increased the Ni 2+ adsorption capacity of PPCB. The molecular dynamic results indicated the carboxylate structures had the strongest adsorption capacity. Moreover, the Ni 2+ removal efficiency of KMnO4 modified biomass decreased linearly with the increase of lignin content in biomass, while KMnO4 modified lignin showed a good adsorption performance, indicating that the cross-linked structures between lignin and other components in the biomass could inhibit the adsorption capacity of PPCB. GRAPHICAL ABSTRACT: UF0001